1992
DOI: 10.1021/bi00155a035
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate both activates and inactivates bleomycin by free radical generation

Abstract: ABSTRACT:The chemotherapeutic agent bleomycin (BLM) is activated by reducing agents to break isolated DNA. Paradoxically, these same reducing agents protect cellular DNA from BLM damage. To resolve this paradox, we have examined the reaction of FelIIBLM with DNA in the presence of ascorbate. As expected, ascorbate augments FeII'BLM-induced DNA damage. However, when ascorbate is added to FelIIBLM prior to exposure to DNA, a redox-inactive BLM is produced in a reaction that generates the ascorbyl radical. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The cells were then washed and assayed for rate of spheroplast formation. the reaction with DNA, the ascorbate did not activate a BLM complex with Fe(III) (4,40). ␤-Mercaptoethanol, another reductant, also inhibited BLM-Fe(II)-O 2 -mediated cell wall damage (data not shown).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The cells were then washed and assayed for rate of spheroplast formation. the reaction with DNA, the ascorbate did not activate a BLM complex with Fe(III) (4,40). ␤-Mercaptoethanol, another reductant, also inhibited BLM-Fe(II)-O 2 -mediated cell wall damage (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…We tested two classes of effectors for their effect on BLM-Fe(II)-O 2 -mediated cell wall damage. Reducing agents such as ascorbate protect against BLM in cellular cytotoxicity assays (4,35). In the presence of DNA, ascorbate can initiate BLM-induced strand scission in the presence of Fe(II) or Fe(III), whereas in the absence of DNA, ascorbate reacts with BLM to produce the ascorbyl radical and a redox-inactive BLM incapable of nicking DNA.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, because cellular reducing factors such as AA can scavenge free radicals and other oxidative species, it has been assumed that such reducing agents would protect cells by suppressing the oxidative processes initiated by bleomycin. Buettner et al demonstrated that both phenomena depend upon whether bleomycin reaching DNA before (DNA damage effect) or after (free radicals scavenging) its interaction with reducing agents [77]. The authors demonstrated that in the presence of DNA, AA initiated bleomycin-induced strand breaks whereas in the absence of DNA, AA reacted with bleomycin to produce the ascorbyl radical and a redox-inactive bleomycin that was incapable of nicking DNA.…”
Section: Vitamin Cmentioning
confidence: 99%
“…The main cellular thiol glutathione (GSH) was noted as a weak activator of DNA nicking by BLM-iron [5]. Ascorbate (Asc), the reduced form of vitamin C, is known as an excellent reducer of Fe(III) and its addition to BLM-Fe(III) reactions stimulated DNA cleavage [14,15]. Although BLM has been extensively used as a tool for the induction of DSBs in cultured cells, how different cellular reducers contribute to the activation of BLM is poorly understood.…”
Section: Introductionmentioning
confidence: 99%